Molding resin raw material composition, microporous membrane resin raw material composition, and manufacturing method thereof
The resin raw material composition, with coated pellets and integrated powder, addresses uneven distribution and dust issues in extrusion molding, enhancing moldability and physical properties of films and microporous membranes.
Patent Information
- Application Number
- JP2022571716
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-25
- Filing Date
- 2021-12-24
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-12-24
AI Technical Summary
Conventional methods for blending resin pellets and powder in extrusion molding face issues with uneven composition distribution, classification, dust generation, and poor moldability, particularly in the production of microporous membranes for lithium-ion secondary batteries, leading to variations in film thickness, fish eyes, and decreased product strength.
A resin raw material composition is developed where resin pellets are coated with a liquid component, and powder is attached to this coating, maintaining a specific ratio of pellets to powder and liquid, with controlled granule formation to ensure uniform distribution and reduced dust generation, using a method that includes blending and kneading steps to integrate the components effectively.
The solution results in improved moldability, reduced dust generation, and enhanced physical properties of the molded products, such as films and microporous membranes, with better dispersibility and handleability, addressing the challenges of classification and uneven composition distribution.
Smart Images

Figure 0007609507000013 
Figure 0007609507000014 
Figure 0007609507000015
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a resin raw material composition for molding, a resin raw material composition for a microporous membrane, and methods for producing the same. [Background technology]
[0002] TECHNICAL FIELD Conventionally, synthetic resins such as general-purpose plastics such as polyethylene, engineering plastics such as polyester, and elastomers, and in particular polyolefin resins such as polyethylene and polypropylene, have a good balance of molded product properties, moldability, weather resistance, and the like, and have been widely used in applications such as packaging films, industrial films for agriculture and the like, blow molding of bottle containers and the like, structural materials, and injection molding of large containers, as well as the production of microporous membranes, etc.
[0003] It is widely known that the pellet or powder-like resin raw materials used for these applications are generally molded by extrusion molding. These resin raw materials are used as a single resin or mixed with inorganic fillers, fiber materials, and the like other than resin. In addition, fillers are often mixed into the resin raw materials to impart functionality, liquid raw materials, for example, liquid plasticizers such as mineral oils (mineral oils) such as liquid paraffin, and additives such as anti-fogging agents such as glycerin esters and antistatic agents are often mixed. Pellets are extruded in Patent Document 1, and powders are extruded in Patent Document 2.
[0004] Many of these resin raw materials are generally sold in the form of pellets with a particle size of about 2 mm to 5 mm, but some are sold as powders with a particle size of about 50 μm to 500 μm. Metal oxides such as alumina, silica, zirconia, and titanium oxide, as well as fillers such as talc, boehmite, and kaolin, are generally sold in powder form with a particle size of about 10 nm to 500 μm. Recently, as described in Patent Document 3, raw materials can also be produced by grinding films or microporous membranes without melting them into chips.
[0005] Recently, the market for microporous membrane separators for lithium ion secondary batteries, particularly for electric vehicles, is growing as an application of microporous membranes. Patent Document 2 also discloses a method for producing such separators for lithium ion secondary batteries.
[0006] In order to improve the functionality of molded products, there are an increasing number of cases where pellets or powders are mixed with liquids for molding. One example of such a case is separators for lithium-ion secondary batteries, in which plasticizers such as liquid paraffin are mixed with resin powders such as polyethylene or polypropylene, extruded, stretched, and then the plasticizer is extracted with a solvent to make the material porous. A common technique is to add plasticizers such as mineral oil to polyethylene, elastomer, and polypropylene pellets to make them flexible.
[0007] Furthermore, ultra-high molecular weight polyethylene resins with a high molecular weight, exceeding 300,000 in viscosity average molecular weight, can be molded to produce molded products or microporous films with extremely high strength, but because the high molecular weight results in an extremely high melt viscosity and makes extrusion molding difficult, they are generally not sold in pellet form, but in polymerized powder form. When mixing this ultra-high molecular weight polyethylene powder with pellets of ordinary polyethylene or polypropylene to increase strength, it is necessary to mix the pellets and powder before use.
[0008] These conventional techniques are based on feeding pellets or powder alone, or after previously blending as necessary, into an extruder, and this method is widely used. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Japanese Patent Publication No. 59-39536 [Patent Document 2] JP 2002-194132 A [Patent Document 3] JP 2006-21519 A [Patent Document 4] JP 2019-142002 A Summary of the Invention [Problem to be solved by the invention]
[0010] However, in the conventional technologies, problems existed in molding processability and product properties, particularly when pellets and powder are blended and simultaneously extruded, especially for use in film molding, and when pellets and powder are blended and simultaneously extruded for use in producing a microporous membrane.
[0011] <Molding processability issues> In the manufacture of a molding resin raw material composition, a method is generally used in which pellets and powder are blended in advance in large quantities using a tumbler mixer, Henschel mixer, or the like. This method allows for large-scale processing, which reduces production costs. In this case, the pellets and powder are first classified during piping transport or in a stationary hopper, which tends to cause unevenness in the composition distribution. The reason for this is that compared to pellets with a particle size of several mm, powders are generally small, ranging from several μm to several hundred μm, so the pellets and powder are classified during piping transport or in a stationary hopper, which tends to cause unevenness in the composition distribution. For example, if resin pellets of about 3 mm and inorganic fillers of about 5 μm or less are mixed in a weight ratio (resin pellets:inorganic filler) of about 8:2 and filled into a hopper with a diameter of 500 mm, a height of 1000 mm, and a capacity of 100 liters, the classification gradually occurs during operation and the powder settles. As a countermeasure, it was possible to install agitators at various points in the process, but this did not provide a fundamental solution because the material would be classified again immediately downstream of the agitators. Also, because powder raw materials are light, they tend to float in the air as dust, which can easily worsen the working environment, especially around the resin raw material supply port of the extruder (hereinafter, this may be referred to as "dust generation").
[0012] In the manufacture of resin raw material compositions for microporous membranes such as separators, generally, an extrusion molding method is used in which a single or multiple resin raw materials are mixed and fed into an extruder. Extrusion molding is widely used in film molding, blow molding, fiber molding, injection molding, etc., because it is easy to obtain molded products at low cost. However, when pellets, filler, and resin powder are simultaneously fed into an extruder, classification occurs in a general dry blend due to the difference in size, and the distribution of each raw material component is likely to be insufficient. Therefore, if they are fed directly into the extruder, the dispersion and mixing in the extruder becomes non-uniform, and the film thickness is likely to vary due to fluctuations in the extrusion state. For example, in film molding by the inflation method, silica for opening the bubbles and blocking inhibitors such as calcium carbonate are used. However, this method also requires kneading the pellets with silica, calcium carbonate, etc. in advance, which increases the manufacturing cost.
[0013] In particular, in separators using a wet method, which is currently widely used as separators for lithium-ion secondary batteries, resin powders with small particle sizes are generally used as raw materials in order to swell the resin with a plasticizer. However, in recent years, the use of pellet raw materials for various purposes has been increasing. As the main raw material, commercially available polyolefin, is more widely available in pellet form than in powder form, it is expected that pellets will be used more frequently in the future for the purpose of reducing costs. In addition, if the pellets are used, it is possible to use masterbatches with various functions, such as masterbatches containing slip agents, antistatic agents, and fillers, together with the pellets. In addition, with the recent increase in momentum for global environmental conservation, the recycling of raw materials has been promoted even in extrusion molding applications. In many cases, recycled raw materials are crushed from films or molded products and melt-pelletized in an extruder, so in order to use recycled raw materials, they must be used as pellets. Thus, it is expected that the need to use these pellet-shaped resin raw materials together with powders will increase in the future for separator applications as well.
[0014] One common method for simultaneously feeding pellets and powder into an extruder and molding with high quality is to optimize the screw shape of the extruder, increase the shaft length of the screw, and increase the time for kneading. These methods increase the energy required for kneading, so that larger and more specialized equipment is required, which increases the production cost. In addition, because the particle sizes of the powder and pellets are significantly different, classification occurs in the feed hopper, for example, just before feeding into the extruder, and good molding cannot be achieved. Thus, in the conventional technology, a raw material composition in which the pellets and powder are not classified when fed into an extrusion kneader cannot be obtained, and there was no method for mixing the pellets and powder well.
[0015] More specifically, compared to pellets with a particle size of several mm, powders are generally small, ranging from several μm to several hundred μm, so that the pellets and powder are classified during piping transport or in a stationary hopper, and the composition distribution is likely to become uneven. For example, if resin pellets of about 3 mm and inorganic fillers of about 5 μm or less are mixed in a weight ratio (resin pellets:inorganic filler) of about 8:2 and filled into a hopper with a diameter of 500 mm, a height of 1000 mm, and an effective capacity of about 100 liters, classification will gradually occur during operation and the powder will settle. As a countermeasure against this, measures such as installing agitators at various points in the process can be taken, but since the powder will be classified again immediately downstream of the installation points, it is not a fundamental solution. In addition, since the powder raw material is light, it is likely to float in the air as dust, and it is particularly likely to worsen the working environment around the resin raw material supply port of the extruder (hereinafter, it may be written as "dust generation").
[0016] Product physical property issues When the composition distribution becomes uneven due to classification as described above, the film thickness tends to fluctuate due to the fluctuation of the extrusion state as described above, and therefore the resulting extrusion molded product, such as a film, and the resulting microporous film, such as a separator, tend to have fish eyes and unmelted gels due to insufficient kneading, worsening thickness unevenness in the film surface, and strength unevenness. Even if the composition distribution unevenness is eliminated to an acceptable level, the difference in the shape of the pellets and the powder, especially the difference in their particle diameter, causes a difference in the melting speed (time until melting) in the extruder, and large pellets may remain unmelted, or conversely, the surface of the pellets may dissolve early and cling to the powder, preventing the kneading energy from being transmitted to the powder, resulting in the powder remaining unmelted. When such a phenomenon occurs, it also leads to fluctuations in the extrusion pressure and extrusion amount. Although the above problem can be solved by melting and pelletizing the necessary raw materials in advance using a twin-screw kneader or the like, the same phenomenon occurs when feeding the raw materials into the twin-screw kneader, and this does not provide a fundamental solution. In addition, the number of manufacturing steps increases, significantly increasing production costs, and further, deterioration due to heat and shear caused by passing the material through multiple extruders increases, tending to result in a decrease in overall strength.
[0017] As described above, all of the above methods have problems with molding processability and / or product properties, and the conventional solutions not only increase production costs, but also narrow the range of applicable component combinations due to differences in pellet and powder size and mixing amounts, necessitating fine adjustments for each component. These problems are particularly important for microporous membranes for lithium ion secondary battery separators, which have recently become thinner.
[0018] In view of the above circumstances, the present disclosure provides a molding resin raw material composition that has good dispersibility, piping transportability, and moldability, has little dust generation and classification, and can give a molded article or a microporous film with good physical properties; Microporous membrane The present invention provides a resin raw material composition for use in moldings and a method for producing the same. [Means for solving the problem]
[0019] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have discovered that the above problems can be solved by using a resin raw material composition that satisfies specific requirements, and have also discovered a method for producing such a resin raw material composition.
[0020] Examples of embodiments of the present disclosure are listed below. [1] A resin raw material composition comprising resin pellets (PL), powder (PW) and a liquid component (LQ), The resin raw material composition is a molding resin raw material composition, At least a part of the surface of the resin pellet is coated with the liquid component, and the resin pellet coated with the liquid component is a single particle or an aggregate of multiple particles, and the powder is attached to the liquid component. Based on the total mass of the resin raw material composition, a ratio of the mass% of the resin pellets to the mass% of the powder (PL / PW) is 0.01 or more and 100 or less, and a ratio of the mass% of the resin pellets to the mass% of the liquid component (PL / LQ) is 1 or more and 199 or less, A resin raw material composition, in which the number of granules containing aggregates of 10 or more of the resin pellets is 20% or less based on the total number of granules. [2] A resin raw material composition comprising resin pellets (PL), powder (PW) and a liquid component (LQ), The resin raw material composition is a resin raw material composition for a microporous membrane, At least a part of the surface of the resin pellet is coated with the liquid component, and the resin pellet coated with the liquid component is a single particle or an aggregate of multiple particles, and the powder is attached to the liquid component. Based on the total mass of the resin raw material composition, a ratio of the mass% of the resin pellets to the mass% of the powder (PL / PW) is 0.01 or more and 100 or less, and a ratio of the mass% of the resin pellets to the mass% of the liquid component (PL / LQ) is 1 or more and 199 or less, A resin raw material composition, in which the number of granules containing aggregates of 10 or more of the resin pellets is 20% or less based on the total number of granules. [3] 3. The resin raw material composition according to item 1 or 2, comprising, as a main component, a granular body in which the powder is attached to the liquid component of the resin pellets coated with the liquid component. [4] The resin raw material composition according to any one of items 1 to 3, wherein the number of granules including a single particle or an aggregate of 2 to 9 particles of the resin pellets is 95% or more based on the total number of granules, and granules having a particle size of 10 mm or more are 1 mass% or less based on the total mass of the resin raw material composition. [5] 5. The resin raw material composition according to any one of items 1 to 4, wherein the number of granules containing a single particle of the resin pellet is 70% or more based on the total number of granules, and the maximum diameter of the granules containing a single particle of the resin pellet is equal to or larger than the particle diameter of the resin pellet and equal to or smaller than the particle diameter of the resin pellet + 5 mm. [6] The number of granular bodies including agglomerates of multiple resin pellets is less than 30% based on the total number of granular bodies, and 6. The resin raw material composition according to any one of items 1 to 5, wherein, when the resin raw material composition further contains granules consisting of the powder and the liquid component and does not contain the resin pellets, the number of granules not containing the resin pellets is less than 20% based on the total number of granules. [7] 7. The resin raw material composition according to any one of items 1 to 6, wherein the number of granules containing aggregates of 10 or more of the resin pellets is 1% or less based on the total number of granules. [8] 8. The resin raw material composition according to any one of items 1 to 7, wherein the resin pellets contain at least one selected from the group consisting of polyolefin, PET, polyamide, aramid, polyvinyl chloride, synthetic rubber, ABS, and PPE. [9] 9. The resin raw material composition according to any one of items 1 to 8, wherein the powder contains at least one selected from the group consisting of polyethylene, elastomer, PET, polyamide, aramid, and inorganic particles.
[10] 10. The resin raw material composition according to any one of items 1 to 9, wherein the powder has a particle size of 10 nm or more and 50 μm or less.
[11] 11. The resin raw material composition according to any one of items 1 to 10, wherein the liquid component is at least one selected from the group consisting of lubricating oil, mineral oil, and liquid paraffin.
[12] 12. The resin raw material composition according to any one of items 1 to 11, wherein the variation in bulk density of the resin raw material composition is 10% or less.
[13] 13. The resin raw material composition according to any one of items 1 to 12, wherein the resin raw material composition has an angle of repose of 30° or more and 55° or less.
[14] A method for producing a resin raw material composition, comprising: The resin raw material composition is a molding resin raw material composition, a coating step of kneading the resin pellets and the liquid component in a blender to coat at least a part of the surface of the resin pellets with the liquid component; a bonding step of feeding a powder into the blender after the coating step, further mixing the powder, and bonding the powder to the liquid component of the resin pellets coated with the liquid component; A method for producing a resin raw material composition comprising the steps of:
[15] Item 15. The method for producing a resin raw material composition according to item 14, wherein the torque rise time is 150 seconds or less.
[16] A method for producing a resin raw material composition, comprising: The resin raw material composition is a resin raw material composition for a microporous membrane, a coating step of kneading the resin pellets and the liquid component in a blender to coat at least a part of the surface of the resin pellets with the liquid component; a bonding step of feeding a powder into the blender after the coating step, further mixing the powder, and bonding the powder to the liquid component of the resin pellets coated with the liquid component; A method for producing a resin raw material composition comprising the steps of:
[17] Item 17. The method for producing a resin raw material composition according to item 16, wherein a torque rise time is 150 seconds or less.
[18] A step of producing a resin raw material composition by the method for producing a resin raw material composition according to item 16 or 17; a step of further mixing the resin raw material composition with resin pellets (PL) and / or powder (PW), which may be the same as or different from the resin pellets (PL) and powder (PW); A method for producing a mixed composition comprising the steps of: Effect of the Invention
[0021] According to the present disclosure, there is provided a molding resin raw material composition that, when used particularly for film or microporous membrane applications, can give products that are excellent in various physical properties such as strength, optical properties, and foreign matter in molding processing, and that has excellent moldability and handleability. According to the present disclosure, there is also provided a microporous membrane resin raw material composition that can give microporous membranes that are excellent in various physical properties, and that has excellent moldability and handleability. Therefore, the molding resin raw material composition of the present disclosure is particularly well used for molding films and microporous membranes. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a photograph of a granular body of the resin raw material composition of the present disclosure. [Diagram 2] FIG. 2 is a photograph of a granular body of a conventional resin raw material composition. [Diagram 3] FIG. 3 is a graph showing the relationship between the kneading time and the average torque (torque rise time) for the resin raw material composition of Example 1.1 and the resin raw material composition of Comparative Example 1.1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] 《Resin raw material composition》 The resin raw material composition of the present disclosure includes pellets, powder, and liquid components (hereinafter, these may be referred to as "PL", "PW", and "LQ", respectively). The resin raw material composition is a resin raw material composition for molding, or a resin raw material composition for a microporous membrane. The resin raw material composition includes a large number of granules, and the granules include a granule having one pellet or an aggregate of multiple pellets, the entire or partial surface of the pellet is covered with a liquid material, and further, a powder is attached to the liquid material (hereinafter, these may be referred to as "PWL" in the present specification). In the present specification, a granule having one (single grain) resin pellet may be referred to as "PWL1", and a granule having an aggregate of multiple resin pellets may be referred to as "PWL2", "PWL3", etc., based on the number of resin pellets. A granule not including a resin pellet, consisting of a powder and liquid components, and having a sieve diameter of 1 mm to 10 mm may be referred to as "PWL0". "Total number of granules" means the total number of granules with PWL0 and PWL1 or higher.
[0024] The resin raw material composition preferably contains pellets, powder, and liquid components as main components. Here, "main components" means that the total mass of the pellets, powder, and liquid components is 50 mass% or more, preferably 70 mass% or more, more preferably 90 mass% or more, and may be substantially 100 mass% based on the total mass of the resin raw material composition. In addition to the main components, the resin raw material composition may also contain other components such as additives and modifiers, as described later.
[0025] <Resin pellets> As the resin pellets (PL), commercially available resin pellets that are generally used may be used. Any resin may be used as the resin of the resin pellets, and for example, the resin may be selected from polyolefin, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyacrylonitrile (PAN), polyamide, aramid, polyvinyl chloride, synthetic rubber, acrylonitrile-butadiene-styrene copolymer resin (ABS), polyphenylene benzobisoxazole (PPE), and the like. The material of the resin pellets is preferably at least one selected from the group consisting of polyolefin, PET, polyamide, aramid, polyvinyl chloride, synthetic rubber, ABS, and PPE. The resin pellets preferably contain polyolefin as a main component. The term "main component" means 50% by mass or more, preferably 70% by mass or more, more preferably 90% by mass or more, based on the total mass of the resin pellets, and may be substantially 100% by mass. Examples of polyolefins include polypropylene (PP), polyethylene (PE), and olefin-based elastomers.
[0026] The polypropylene is not particularly limited, and examples thereof include propylene homopolymers such as isotactic polypropylene (IPP), syndiotactic polypropylene, and atactic polypropylene; random copolymers (RPP), block copolymers (BPP), and terpolymers obtained by copolymerizing propylene with comonomers such as ethylene, butene, and α-olefins having 5 or more carbon atoms, etc. These may be used alone or in mixture.
[0027] The viscosity average molecular weight (Mv) of the resin of the resin pellets is preferably 1 million or less, more preferably 700,000 or less, and even more preferably 600,000 or less, since melt kneading becomes easy and, as a result, fish-eye defects tend to be improved when the resin raw material composition is made into a film or a microporous membrane. From the viewpoint of strength, the viscosity average molecular weight of the resin of the resin pellets is 100,000 or more, more preferably 200,000 or more. When the resin pellets are polypropylene, from the same viewpoint, the viscosity average molecular weight (Mv) of the polypropylene is preferably 1 million or less, more preferably 700,000 or less, and even more preferably 600,000 or less, preferably 100,000 or more, and more preferably 200,000 or more.
[0028] Here, as defined in Polymer Dictionary, Editorial Committee on Polymer, Taiseisha, 2000, 6th reprint, p. 337, etc., fisheye refers to a small spherical mass occurring in a film-like or sheet-like molded product or in a microporous membrane, and was given this name because many of them show transparency like a fish's eye. Fisheyes can be distinguished from each other based on the cause of their formation, and include various types such as unmelted masses caused by insufficient kneading of the molding material, masses where a part of the raw material has gelled, masses caused by partial deterioration of the material during molding, and masses with foreign matter as the nucleus. However, in this specification, fisheyes are caused by the material of the resin raw material composition used as the raw material of the molded product, and those with foreign matter as the nucleus are excluded. The foreign matter can be, for example, cellulose, dust, metal pieces, carbonized resin, different types of plastics, lint, and pieces of paper.
[0029] The resin of the resin pellets is preferably a polypropylene whose stereoregularity is controlled by using a metallocene catalyst or a resin obtained by blending BPP or RPP in an amount of 0.5 to 30% by mass with IPP. By using such a polypropylene, permeability tends to be improved, for example, in microporous membrane applications.
[0030] The resin of the resin pellet may be a mixture of polyethylene and polypropylene. Examples of polyethylene include high density polyethylene, ultra-high molecular weight polyethylene, linear low density polyethylene, high pressure low density polyethylene, and mixtures thereof. In addition, polyethylene with a narrow molecular weight distribution using a metallocene catalyst, high density polyethylene, and polyethylene by multi-stage polymerization may be used. Among the above, it is preferable to use linear high density polyethylene by ion polymerization, ultra-high molecular weight polyethylene, or a mixture thereof, from the viewpoint of reducing heat shrinkage when forming a film or a microporous membrane. The ultra-high molecular weight polyethylene here refers to polyethylene with a viscosity average molecular weight of 500,000 or more. The proportion of ultra-high molecular weight polyethylene in the total polyethylene is preferably 5 to 50% by mass, and more preferably 9 to 40% by mass from the viewpoint of dispersibility. However, in this case, the ultra-high molecular weight polyethylene is generally used in a powder form, and in that case, it is classified as "powder".
[0031] The polyethylene preferably contains a polyethylene component having a molecular weight of less than 10,000. The polyethylene component having a molecular weight of less than 10,000 here refers to a portion having a molecular weight of less than 10,000 in a chart of molecular weight distribution measured by gel permeation chromatography (GPC), and the proportion can be determined from the area ratio on the chart. When a polyethylene component having a molecular weight of less than 10,000 is produced under specific conditions, a part of the polyethylene component migrates to the surface of the microporous film, and as a result, it has the effect of reducing the amount of polypropylene on the surface. As a method for including such a polyethylene component having a molecular weight of less than 10,000 in polyethylene, the polyethylene may be produced by setting polymerization conditions so that a large amount of low molecular weight components are contained during polymerization of polyethylene, or the polyethylene may be produced by mixing a polyethylene component having a weight average molecular weight of less than 10,000 with a normal polyethylene.
[0032] The content of the polyethylene component having a molecular weight of less than 10,000 is preferably 5% by mass or more relative to the total polyethylene amount. Within this range, friction during film or microporous membrane production tends to be reduced, and productivity tends to be improved. More preferably, it is 10% by mass or more. Within this range, winding processability in the secondary processing step of these films and microporous membranes tends to be improved. Furthermore, if it is 20% by mass or more, even higher speed processing becomes possible, and productivity tends to be improved. On the other hand, from the viewpoint of improving the strength of the film or microporous membrane, it is preferably 50% by mass or less. Also, from the viewpoint of further improving friction reduction, it is preferable that the polyethylene component having a molecular weight of less than 1,000 is contained at 1% by mass or more.
[0033] The resin of the resin pellet may contain, as a resin other than polypropylene and polyethylene, polybutene-1 resin, propylene-based elastomer, ethylene-based elastomer, particularly a random copolymer elastomer of propylene and ethylene, for the purpose of improving film-forming properties. Polymethylpentene-1 resin may also be used, and one having a melt flow rate (MFR) of 0.01 to 30 g / 10 min is preferably used. Particularly preferably, it is within the range of 0.1 to 5 g / 10 min.
[0034] In addition to the above, the resin of the resin pellets may be a thermoplastic resin selected from engineering plastic resins such as polyphenylene ether, polyamide resins such as nylon 6, nylon 6-12, and aramid resin, polyimide resins, polyester resins such as PET and PBT, polycarbonate resins, fluororesins such as polyvinylidene fluoride (PVDF), copolymers of ethylene and vinyl alcohol, copolymers of C2 to C12 α-olefins and carbon monoxide and hydrogenated products thereof, hydrogenated styrene polymers, copolymers of styrene and α-olefins and hydrogenated products thereof, copolymers of styrene and aliphatic monounsaturated fatty acids, polymers of acrylic acid and its derivatives, copolymers of styrene and conjugated diene unsaturated monomers, and hydrogenated products thereof.
[0035] From the viewpoint of extrusion moldability, the particle diameter of the resin pellets is preferably in the range of about 1 mm to 10 mm, more preferably 2 mm to 6 mm, and further preferably 3 mm to 5 mm. The method for producing the pellets is not limited, but for example, in the case of high-density polyethylene, polyethylene powder having a particle diameter of several tens to several hundreds of μm polymerized by a low pressure method is melt-kneaded in an extruder heated to about 200° C., and then cut into a particle diameter size of about 1 mm to 5 mm by strand cutting or underwater cutting. Pellets produced by crimping and cutting a film once formed by the method shown in Patent Document 4 can also be used.
[0036] The proportion of the resin pellets in the total mass of the resin raw material composition is preferably 5% by mass to 98% by mass, and more preferably 30% by mass to 98% by mass.
[0037] <powder> Powder (PW) refers to fine particles with a particle diameter of several nm to several hundreds μm. The proportion of the powder in the total mass of the resin raw material composition is preferably 5 mass% to 90 mass%, more preferably 8 mass% to 50 mass%. The powder is preferably resin particles, inorganic particles, etc., but may also be crushed fibers, natural substances such as wood chips, metal fine particles, etc.
[0038] The resin particles may be, for example, the resins listed as the resin pellets described above. The type and molecular weight of the resin are as described in the resin pellet section, so they will not be described here. The resin particles may be produced by pulverizing polymerized resin or its pellets.
[0039] Examples of the resin particles include powders of polyethylene, polypropylene, elastomer, PET, polyamide, and aramid, among the resins listed as the resin pellets. The resin particles preferably contain polyolefin as a main component. The "main component" means 50% by mass or more, preferably 70% by mass or more, more preferably 90% by mass or more, and may be substantially 100% by mass, based on the total mass of the resin pellets. The polyolefin preferably includes polyethylene, polypropylene, and olefin-based elastomers, and more preferably polyethylene.
[0040] The viscosity average molecular weight (Mv) of the resin particles is preferably 200,000 or more, more preferably 300,000 or more, from the viewpoint of improving the strength of the film or microporous membrane. The upper limit of the viscosity average molecular weight (Mv) is preferably 10 million or less, more preferably 5 million or less, from the viewpoint of extrusion moldability and stretchability. The viscosity average molecular weight (Mv) of the polyethylene powder (when multiple types of polyethylene are used, the viscosity average molecular weight of the entire polyethylene) is preferably 200,000 or more, more preferably 300,000 or more, from the viewpoint of improving the strength of the film or microporous membrane. The upper limit of the viscosity average molecular weight (Mv) is preferably 10 million or less, more preferably 5 million or less, from the viewpoint of extrusion moldability and stretchability. The molecular weight distribution (Mw / Mn) of the polyethylene powder is preferably 5 or more, more preferably 8 or more, from the viewpoint of improving the kneadability when mixing and kneading inorganic fillers and suppressing the occurrence of granular defects caused by secondary aggregation of inorganic fillers. As described above, from the viewpoint of reducing heat shrinkage when forming a film or a microporous membrane, ultra-high molecular weight polyethylene powder may be used.
[0041] The diameter of the resin particles is smaller than the size of the pellets, and preferably the average diameter is 300 μm or less. When the diameter is 300 μm or less, the reaction time during the production of the polymer powder is short, and the productivity is excellent. The diameter of the resin particles is preferably 200 μm or less, more preferably 100 μm or less. The lower limit is not particularly limited, but is appropriately adjusted from the viewpoint of dust explosion during air transportation during molding, and can be, for example, 10 μm or more, 50 μm or more, or 100 μm or more.
[0042] The proportion of the resin particles in the total mass of the resin raw material composition is preferably 5% by mass to 90% by mass, and more preferably 10% by mass to 50% by mass.
[0043] Examples of inorganic particles include oxide ceramics such as alumina (e.g., α-alumina, etc.), silica, titania, zirconia (including yttria-modified zirconia), magnesia, ceria, yttria, zinc oxide, and iron oxide; nitride ceramics such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, aluminum sulfate, aluminum hydroxide, potassium titanate, talc, kaolin clay, kaolinite (kaolin), halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fibers, which may be used alone or in combination. Among these, the inorganic particles are preferably at least one selected from the group consisting of silica, alumina, zeolite, kaolin, talc, zirconia, and titania.
[0044] The proportion of the inorganic particles in the total mass of the resin raw material composition is preferably 3% by mass to 90% by mass, and more preferably 5% by mass to 55% by mass.
[0045] The particle size of the inorganic particles is not particularly limited, but is, for example, 10 nm or more and 50 μm or less. In addition, various particle sizes can be used depending on the purpose. For example, when hydrophobic inorganic particles are used to improve wettability with an organic solvent, particles having a relatively small average particle size, for example, 5 nm to 1 μm, preferably about 5 nm to 100 nm, may be used to improve dispersibility in the resin and surface area. On the other hand, when inorganic particles having an average particle size of 1 μm to 10 μm are used, the strength of the film or microporous membrane tends to be improved, and further, when inorganic particles having an average particle size of 1.5 μm to 5 μm are used, the uneven thickness during film formation tends to be improved. The bulk density (bulk density) of the inorganic particles is 0.05 g / cm 3 ~10g / cm 3 and preferably 0.1 to 5 g / cm 3 These powders may be used alone or in combination of two or more kinds.
[0046] <Liquid components> By including a liquid component, the resin raw material composition can integrate the pellets and the powder, suppressing dust generation due to the powder. The liquid component (LQ) is not particularly limited as long as it is liquid and can suppress dust generation, and is preferably a lubricating oil or mineral oil used as a plasticizer when producing a molded product or a microporous film, and may be phthalates such as dioctyl phthalate (DOP) and dibutyl phthalate (DBP), liquid paraffin, other plasticizers, softeners, and anti-fogging agents that contribute to the performance expression of the product obtained by extrusion molding. The liquid component (LQ) is preferably at least one selected from the group consisting of lubricating oil, mineral oil, and liquid paraffin. In addition, when the molded product is used for a microporous film, most or all of the plasticizer such as liquid paraffin is removed from the final product. Due to the action of this liquid component, powders that are generally easy to classify from pellets and have the property of flying up as dust in the work area, for example, nanofillers with a particle size of about 5 nm to 50 nm, can be used well.
[0047] The viscosity of the liquid component is not particularly limited. When using a resin powder having a relatively large particle size, for example, 100 μm or more, the viscosity is preferably relatively high. Preferably, the kinetic viscosity at 40° C. (JIS K 2283) is 50 mm 2 / S or more, more preferably 60 mm 2 A high viscosity means that the powder adheres well to the pellets and is less likely to separate from the pellets during transportation.
[0048] The proportion of the liquid component in the total mass of the resin raw material composition is preferably 0.1 mass % to 30 mass %, and more preferably 2 mass % to 7 mass %.
[0049] <Granular body> The granules are formed by coating at least a portion of the surface of resin pellets with a liquid component, the resin pellets coated with the liquid component being in the form of a single particle or an aggregate of multiple particles, and powder adhering to the liquid component. The number of granules containing aggregates of 10 or more resin pellets (PWL10 or higher) is 20% or less based on the total number of granules. The small number of PWL10 or higher results in less classification, and can provide a resin raw material composition that is excellent in dispersibility, piping transportability, moldability, and various physical properties obtained.
[0050] In order to obtain such a resin raw material composition with a small number of PWL10 or more, it is desirable that the weight mixing ratio of PL, LQ, and PW is appropriate. First, the ratio of the mass% of the resin pellets to the mass% of the powder (PL / PW) is preferably about 99.01 / 0.99 to 1 / 99 (0.01 to 100), more preferably 99 / 1 to 1 / 99 (0.01 to 99), even more preferably 95 / 5 to 50 / 50 (1 to 19), particularly preferably 95 / 5 to 66.7 / 33.3 (2 to 19), and particularly preferably 90 / 10 to 70 / 30 (2.3 to 9). For example, PL / PW is preferably 2 or more and 100 or less. Above the upper limit, the resin raw material composition becomes sticky, making it difficult to transport through a pipeline, whereas below the lower limit, adhesion between the pellets and powder is insufficient, which makes separation likely to occur and generates dust due to the powder.
[0051] The ratio of the mass% of the resin pellets to the mass% of the liquid component (PL / LQ) is 99.5 / 0.5 (upper limit) to 50 / 50 (lower limit) (1 to 199), preferably 99 / 1 (upper limit) to 50 / 50 (lower limit) (1 to 99), more preferably 99 / 1 (upper limit) to 70 / 30 (lower limit) (2.3 to 99), even more preferably 98 / 2 (upper limit) to 70 / 30 (lower limit) (2.3 to 49), and even more preferably 97 / 3 (upper limit) to 80 / 20 (lower limit) (4 to 32.3). Within this range, the dispersibility is stable. If the upper limit is exceeded, it becomes difficult for the PL to be covered with the LQ, and dust and classification are likely to occur. If the lower limit is exceeded, the LQ becomes excessive, causing stickiness, and the piping transportability tends to deteriorate.
[0052] The ratio of the mass% of the powder to the mass% of the liquid component (PW / LQ) is preferably in the range of 99 / 1 (upper limit) to 20 / 80 (lower limit) (0.25-99), more preferably 95 / 5 (upper limit) to 30 / 70 (lower limit) (0.43-19), and even more preferably 90 / 10 (upper limit) to 40 / 60 (lower limit) (0.67-9). When mixed at this mixing ratio and kneaded by a suitable means such as a tumbler mixer or Henschel mixer, the outer surface of the pellet is covered with the liquid component, making it easy to moderately adhere the powder to the resin pellet. By making the ratio 0.25 or more, the adhesion of the powder is improved, and by making the ratio 99 or less, the stickiness of the resin raw material composition due to the liquid component is suppressed, and the piping transportability tends to be improved.
[0053] In the resin raw material composition, the maximum diameter of the granular material (PWL1) containing single resin pellets is preferably equal to or larger than the particle diameter of the resin pellets, more preferably larger than the particle diameter of the resin pellets, and is preferably equal to or smaller than the particle diameter of the resin pellets + 5 mm, more preferably equal to or smaller than the particle diameter of the resin pellets + 4 mm, even more preferably equal to or smaller than the particle diameter of the resin pellets + 3 mm, even more preferably equal to or smaller than the particle diameter of the resin pellets + 2 mm, and even more preferably equal to or smaller than the particle diameter of the resin pellets + 1 mm. When the maximum diameter of the granular material (PWL1) containing single resin pellets is within the above range, there are fewer granular materials with excessive powder attached to the surface of the resin pellets, which further suppresses classification, and tends to further improve piping transportability.
[0054] The resin raw material composition preferably contains as a main component granules in which powder is attached to the liquid component of resin pellets coated with the liquid component. Here, the "main component" means that the granules account for 50% by mass or more of the total mass of the resin raw material composition, preferably 70% by mass or more, more preferably 90% by mass or more, and may be substantially 100% by mass.
[0055] From the viewpoints of handling, low dust generation, and moldability, the number of single-grain granules (PWL1) and 2-9 granules (PWL2-9) is preferably 95% or more based on the total number of granules; and the number of granules having a particle size of 10 mm or more is preferably 1 mass% or less based on the total mass of the resin raw material composition. From the same viewpoint, the number of granules containing multiple resin pellets is preferably less than 30%, more preferably less than 20%, based on the total number of granules; and when the resin raw material composition further contains granules (PWL0) consisting of powder and liquid components not containing resin pellets, the number of PWL0 is preferably less than 20%, more preferably less than 10%, based on the total number of granules. However, PWL0 means a sieve diameter of 1 mm or more and 10 mm or less. If there are many agglomerates having a size of less than 1 mm or more than 10 mm, the dispersion state is deteriorated. From the same viewpoint, the number of granules containing 10 or more resin pellets (PWL10 or more) is 20% or less, preferably 1% or less, and more preferably substantially none, based on the total number of granules.
[0056] It is particularly preferred that the number of PWL1 is 70% or more based on the total number of granules, and the maximum diameter of the granules (PWL1) including a single resin pellet is equal to or larger than the particle diameter of the resin pellet and equal to or smaller than the particle diameter of the resin pellet + 5 mm. By making the number of PWL1 equal to or larger than a certain percentage and reducing the maximum diameter, a resin raw material composition that is particularly excellent in terms of handling, low dust generation, and moldability can be obtained.
[0057] <Bulk density> The bulk density of the resin raw material composition depends greatly on the specific gravity, particularly when an inorganic filler is used, but for general use as a raw material, it is preferably 0.1 g / cm 3 ~2g / cm 3 , more preferably 0.3 g / cm 3 ~1.5g / cm 3 , more preferably 0.5 g / cm 3 ~1.2g / cm 3The variation in bulk density is preferably 10% or less, more preferably 5% or less, and even more preferably 3% or less. When the bulk density and its variation are within the above ranges, the amount of material fed to the extruder is stable, and the uniformity of the film product or microporous membrane is improved.
[0058] <Angle of repose> The resin raw material composition preferably has an angle of repose of 30° to 55° inclusive. When the angle of repose is within the above range, the resin raw material composition can be used satisfactorily in the raw material hopper or supply feeder of a general extrusion molding device.
[0059] <Torque rise time> The resin raw material composition preferably has a torque rise time of 150 seconds or less when measured with a Plastomill kneader (manufactured by Toyo Seiki Co., Ltd.). In this specification, the term "torque rise time" refers to the time from the start of kneading until the torque of the Plastomill kneader rises and eventually reaches a peak. A short torque rise time means that the resin pellets and liquid component are sufficiently kneaded in step (a), and the liquid component is adhered almost uniformly to almost the entire surface of the resin pellets. This makes it easy to obtain a stable structure for PWL1, with the maximum diameter of PWL1 being the particle size of the resin pellets + 5 mm or less.
[0060] <Other Ingredients> In addition to the pellet, powder, and liquid components, the resin raw material composition may contain other resin components in other forms, additives such as inorganic fillers, antioxidants, dispersing agents, antistatic agents, processing stabilizers, and crystal nucleating agents, and additives such as organic fillers, for the purpose of property modification, cost reduction, etc. The proportion of each of these components in the resin raw material composition is preferably 5% by mass or less, more preferably 2% by mass or less, and may be substantially 0% by mass.
[0061] Examples of the antioxidant include phenolic antioxidants such as "Irganox 1010", "Irganox 1076" and "BHT" (all trademarks, manufactured by Ciba Specialty Chemicals); phosphorus-based and sulfur-based secondary antioxidants; and hindered amine-based weathering agents, and these can be used alone or in combination depending on the purpose. In particular, a combination of a phenolic antioxidant and a phosphorus-based antioxidant is preferably used. Specifically, pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butylhydroxyphenyl)propionate, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butylhydroxybenzyl)benzene, tris(2,4-di-t-butylphenyl)phosphite, tetrakis(2,4-di-t-butylphenyl)-4,4'-biphenylenephosphite, etc. are preferred. Also preferred are 6-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-t-butyldibenzo[d,f][1,3,2]dioxyphosphepine, etc. The amount of the antioxidant is preferably 100 ppm to 10,000 ppm based on the total mass of the resin pellets in the resin raw material composition. When a phenol-based antioxidant and a phosphorus-based antioxidant are used in combination, the mass ratio of the phenol-based / phosphorus-based antioxidant is preferably 1 / 3 to 3 / 1.
[0062] When the resin raw material composition is used to form a microporous membrane, particularly when the microporous membrane is produced by extrusion molding, the resin raw material composition preferably contains polypropylene resin pellets as resin pellets, and also contains a crystal nucleating agent for the purpose of controlling the crystallinity of the polypropylene and controlling the formation of micropores. The type of crystal nucleating agent is not particularly limited, but includes general benzyl sorbitol-based ("Gelall" (trademark, manufactured by New Japan Chemical Co., Ltd.)), metal phosphates, metal carboxylates such as aluminum t-butyl benzoate, and the like. Specific examples thereof include bis(p-ethylbenzylidene)sorbitol, bis(4-methylbenzylidene)sorbitol, bis(3,4-dimethylbenzylidene)sorbitol, bisbenzylidene sorbitol, and the like. The amount of the crystal nucleating agent to be blended depends on the desired crystallization conditions, but is preferably 100 ppm or more relative to the amount of polypropylene from the viewpoint of rapid crystallization and easy moldability, and is preferably 10,000 ppm or less from the viewpoint of preventing excessive bleeding due to an excess of crystal nucleating agent. The more preferred blending amount of the crystal nucleating agent is 100 ppm to 2,000 ppm relative to polypropylene. In the production of a microporous film using a normal plasticizer, when liquid paraffin or a phthalate ester-based plasticizer is used, a microporous film using polyethylene is likely to exhibit permeability, but polypropylene has smaller pores than polyethylene and tends to have poor permeability. As a means for increasing the permeability of this polypropylene, a method of adjusting the pores to an appropriate size is effective, and for example, the phase separation speed is adjusted by using a crystal nucleating agent, making it easy to form an appropriate pore structure.
[0063] In addition, as a dispersing aid for polypropylene and polyethylene, for example, a hydrogenated styrene-butadiene elastomer, an elastomer copolymerized with ethylene and propylene, etc. can be used as necessary. The amount of these dispersing aids to be added is not particularly limited, but is preferably 1 to 10 parts by mass per 100 parts by mass of the total amount of polypropylene and polyethylene.
[0064] Examples of the antistatic agent include amines such as alkyldiethanolamine and hydroxyalkylethanolamine, amine esters such as stearyldiethanolamine monofatty acid ester, alkylamides such as lauric acid diethanolamide and stearic acid diethanolamide, monofatty acid esters of glycerin and diglycerin, anionic antistatic agents such as alkylbenzenesulfonic acid, and polyoxyethylene alkyl ethers, which may be used alone or in combination. The amount of the antistatic agent to be added is not particularly limited, but is preferably about 500 to 10,000 ppm relative to the total mass of the resin pellets of the resin raw material composition.
[0065] <<Mixed composition containing resin raw material composition>> When the resin raw material composition of the present disclosure is a resin raw material composition for a microporous membrane, the resin raw material composition for a microporous membrane may be used alone to form a microporous membrane, or may be blended with pellets (PL) and / or powder (PW) to form a mixed composition for forming a microporous membrane. That is, a desired mixed composition can be produced using the resin raw material composition for a microporous membrane of the present disclosure as a master batch. The PL and / or PW to be additionally blended may be the same material as the PL and PW contained in the resin raw material composition for a microporous membrane, or may be different materials. For example, a resin raw material composition for a microporous membrane (raw material A) having a PL / PW / LQ=85 / 10 / 5 (weight blend ratio) may be produced using polypropylene pellets as PL, polyethylene powder as PW, and mineral oil as LQ, and a polyethylene powder (raw material B) the same as or different from the polyethylene powder used in raw material A may be further added and blended to obtain a mixed composition. In this case, since PW has already adhered to the PL of raw material A, there is an advantage that the mixed composition is difficult to classify when dry-blended with the PW of raw material B. This method allows the desired composition to be adjusted by a simple method known as dry blending, and therefore can greatly improve productivity.
[0066] <<Method for producing resin raw material composition>> The method for producing a resin raw material composition of the present disclosure includes the following steps (a) and (b) when the resin raw material composition is a molding resin raw material composition. (a) A coating step of kneading resin pellets and a liquid component in a blender to coat at least a part of the surface of the resin pellets with the liquid component. (b) After the coating step, the powder is put into a blender and further kneaded to adhere the powder to the liquid component of the resin pellets coated with the liquid component.
[0067] Each component may be added at once or in several portions. In addition, additives other than the above-mentioned components may be added in this step (a) and / or (b). Pellets and powder may be added not only in (a) but also in (b) as appropriate. As the blender referred to in steps (a) and (b), a blender such as a tumbler mixer or a Henschel mixer is preferably used. These can be used at room temperature. When a tumbler mixer is used in step (b), a lot of powder and pellets adhere to the inside of the blender due to the liquid components after blending, but the raw material in the center where the powder and pellets do not adhere may be used as is, or the adhered matter may be scraped off with a spatula or the like and further blended and mixed with the raw material in the center. The same applies when a Henschel mixer is used in step (b). In the method for producing a resin raw material composition for a microporous membrane, after either step (a) or (b), preferably after step (b), a large particle size lump may be removed using a sieve with an opening diameter of about 10 mm.
[0068] The method for producing a resin raw material composition of the present disclosure includes the following steps (a') and (b') when the resin raw material composition is a resin raw material composition for a microporous membrane. Step (a') A coating step of mixing the resin pellets and the liquid component in a blender to coat at least a part of the surface of the resin pellets with the liquid component. Step (b') is an adhering step in which, after the coating step, the powder is added to a blender and further mixed to adhere the powder to the liquid component of the resin pellets coated with the liquid component.
[0069] Each component may be added at once or in several portions. In this step (a') and / or (b'), additives other than the above-mentioned components may be added. Pellets and powder may be added not only in (a') but also in (b') as appropriate. As the blender referred to in steps (a') and (b'), a blender such as a tumbler mixer or a Henschel mixer is preferably used. These can be used at room temperature. When a tumbler mixer is used in step (b'), a lot of powder and pellets adhere to the inside of the blender due to the liquid components after blending, but the raw material in the center where the powder and pellets do not adhere may be used as is, or the adhered material may be scraped off with a spatula or the like and further blended and mixed with the raw material in the center. The same applies when a Henschel mixer is used in step (b'). In the manufacturing method of the resin raw material composition for microporous membrane, after either of the steps (a') and (b'), preferably after step (b'), a large particle size lump may be removed using a sieve with an opening diameter of about 10 mm.
[0070] In the manufacturing method of the resin raw material composition of the present disclosure, in order to obtain a stable PWL1 having a maximum diameter of the particle size of the resin pellet + 5 mm or less, it is desirable to have an appropriate weight mixing ratio of PL, LQ, and PW. The weight mixing ratio is described in the "Granular body" section, so it is not described here.
[0071] The resulting resin raw material composition preferably has a torque rise time of 150 seconds or less when measured with a plastomill. Details of the torque rise time have been described above, so a detailed description thereof will be omitted here.
[0072] An example of a method for producing a resin raw material composition will be described. In step (a), resin pellets and a liquid component are put into a blender and kneaded. As a result, the surface of the resin pellets is appropriately wetted with the liquid component. Preferably, the entire surface of the resin pellets is uniformly coated with the liquid component. Next, in step (b), a powder is added to the blender and further stirred. Separate blenders may be used for steps (a) and (b), or step (b) may be performed by adding powder to the same blender containing the resin pellets coated with the liquid component produced in step (a). In step (b), the powder adheres to the liquid component on the surface of the resin pellets, and the resin raw material composition of the present disclosure can be obtained. The granules of the obtained resin raw material composition preferably have a maximum diameter of PWL1 that is equal to or less than the particle diameter of the resin pellets + 5 mm, and have a stable structure as PWL1. Next, the resin raw material composition is put into an arbitrary molding device, for example, a hopper of an extruder. The resin raw material composition of the present disclosure is excellent in ease of handling and low dust because it is rarely classified in the hopper and generates little dust. In addition, since the pellets and powder are integrated, classification of the two is unlikely to occur. When kneading is started in the barrel immediately below the hopper of the extruder, each material is quickly dispersed and melted uniformly. Therefore, the resin raw material composition of the present disclosure is also excellent in moldability.
[0073] As an example of steps (a) and (b), a case will be described in which commercially available polyethylene pellets (PL1) are blended with a commercially available antiblocking agent (PW1) as a powder, and mineral oil (LQ1) is kneaded as a liquid component. In step (a), 20 kg of PL1 is first weighed out, LQ1 is added thereto, and the mixture is stirred for 10 minutes in an 80-liter tumbler mixer. This allows the surface of PL1 to be adequately wetted with LQ1. Step (b): Next, PW1 is added, and the mixture is stirred for another 5 minutes. The amounts of the ingredients can be adjusted so that the composition ratio (wt%) after mixing is, for example, PL1 / PW1 / LQ1=92 / 5 / 3. The resin raw material composition thus produced may be sieved through a sieve with an opening of about 10 mm to remove large granular bodies.
[0074] FIG. 1 is an example of a granule of the resin raw material composition (10) of the present disclosure. In this example, the granule contains only one pellet (PWL 1 grain) as the main component. The resin raw material composition may contain a granule having a plurality of pellets of PWL 2 to 10, but the amount is relatively small. In addition, the granules consisting of only powder and liquid components, and powder dust are hardly observed or are substantially absent. This results in excellent handleability, low dust generation, and moldability.
[0075] An example of a conventional method for producing a resin raw material composition will be described. In this method, resin pellets and powder are first put into a blender and kneaded, and then a liquid component is put into the blender and kneaded. Therefore, the entire surface of the resin pellets cannot be uniformly covered with the liquid component, and the obtained resin raw material composition contains large granules formed by the liquid component and the powder, and large granules formed by a large amount of powder gathering around the resin pellets. It is presumed that this is formed by the liquid component adhering to a part with a lot of powder or to the wall of the blender before the liquid component is uniformly attached to the surface of the resin pellets, and a large mass of powder grows on the wall of the blender and falls off. Next, when the resin raw material composition is put into the hopper of the extruder, classification is likely to occur and handling is poor. Even if kneading is started in the barrel directly below the hopper of the extruder, each material is difficult to uniformly disperse and melt, so that the conventional resin raw material composition has poor moldability.
[0076] Another example of a conventional method for producing a resin raw material composition will be described. In this method, resin pellets and powder are put into a blender at once to produce a dry blend resin raw material composition. The resulting resin raw material composition is then put into a hopper of an extruder, but classification is likely to occur, making it difficult to handle, and powder dust is also generated.
[0077] An example of a conventional method for producing a resin raw material composition for a microporous membrane will be described. In this method, a raw material composition in which only a plurality of types of powders are dry-blended is generally used. However, there has been no example of mixing powder and pellets in a wet method. Therefore, in order to simultaneously use powder and pellets in a wet method, the pellets and powder are put into a blender (stirrer) such as a Henschel mixer and dry-blended. However, the powder and pellets have a large difference in particle size and are easily classified. In order to reduce the classification, it is possible to add a liquid component to the mixture, but the liquid component will integrate a plurality of resin pellets and a large amount of powder. As a result, the obtained resin raw material composition for a microporous membrane contains large granules formed by the liquid component and the powder, and large granules formed by a large amount of powder gathering around the resin pellets. It is presumed that this is formed by the liquid component adhering to the powdery parts and the walls of the blender before the liquid component is uniformly attached to the surface of the resin pellets, causing large lumps of powder to grow on the walls of the blender and then collapsing. Next, when the resin raw material composition for a microporous membrane is charged into the hopper of an extruder, classification is likely to occur, making the handling difficult. Even when the resin raw material composition for a microporous membrane is charged into the extruder and kneading is started, each material is unlikely to be uniformly dispersed and melted, so fish eyes frequently occur, and conventional resin raw material compositions for a microporous membrane have poor moldability.
[0078] Another example of a conventional method for producing a resin raw material composition for a microporous membrane will be described. In this method, resin pellets and powder are put into a blender at once to produce a dry-blended resin raw material composition for a microporous membrane. The resulting resin raw material composition for a microporous membrane is then put into the hopper of an extruder, but classification is likely to occur, making it difficult to handle, and powder dust is also generated.
[0079] Fig. 2 shows an example of a granular body of the conventional resin raw material composition (30) produced by the above-mentioned dry blending method. In this example, it can be seen that classification is likely to occur due to the difference in size between the resin pellets and the powder dust, and that the large amount of powder dust causes high dust generation.
[0080] <<Method for producing mixed composition>> The resin raw material composition for microporous membrane of the present disclosure produced in steps (a') and (b') may be further blended with powder and / or pellets to be used as a mixed composition (hereinafter referred to as step (c')). Step (c') may be performed using a general blender such as a Henschel mixer or a tumbler mixer. In step (c'), powder and / or pellets may be added to the blender used in step (b') following step (b'), or a blender different from that used in step (b') may be used. EXAMPLES
[0081] Measurement and evaluation methods <Contents (mass%) of PL, PW and LQ, and the proportion of PWL in the resin raw material composition> The measurement was carried out according to the following procedure. 1. Number of PWL0, PWL1, PWL2 and PWL10 or higher, and percentage of PWL1 to 9 5 g of the resin raw material composition was sampled in a container (approximately 250 to 500 particles). The numbers of particles with PWL 0, 1, 2, and 10 or more were counted, and the respective proportions (number %) were calculated. In addition, the total weight of PWL 1 to 9 was measured, and the proportion (mass %) to the total weight (5 g) was measured. 2. Measurement of the proportions of PL, PW and LQ (mass%) One hundred grains of PWL1 were collected and weighed (W T ) This was washed with a solvent that only the liquid component dissolves (e.g., methylene chloride if the liquid component is liquid paraffin), and the PL and PW were filtered and weighed (W PL+PW ). W T -W PL+PW From the weight of LQ (W LQ ) and weight ratio (mass%) were calculated. Next, PL and PW were sieved and their respective weights (W PL , W PW ) and weight ratio (mass%) were calculated. 3. Measurement of the percentage of particles with a particle size of 10 mm or more (mass%) A 50 g sample (about 2500 to 5000 particles) of the resin raw material composition was placed in a container and classified using a sieve with a mesh size of 10 mm. The weight of particles with a particle size of 10 mm or more was measured, and the ratio (mass %) to the total weight (50 g) was measured.
[0082] <Particle size> For powders, pellets, and granules, particle sizes of approximately 0.05 mm (50 μm) or larger were measured using a Keyence microvideoscope, and for smaller sizes, a scanning electron microscope was used. The particle size was determined as the diameter (maximum diameter) of a circle circumscribing the particle to be measured, and 100 particles were randomly selected and their average was calculated.
[0083] <Dispersion (torque rise time)> Measurements were carried out using a Toyo Seiki Co., Ltd. Plastomill R-60 with a rotor diameter of 30 mm, in the following manner. procedure 1. A resin raw material composition and liquid paraffin were prepared. The amount of liquid paraffin was adjusted so that the amount of both was 30 mass % after mixing, and they were mixed in a cup with a stirring rod. The total weight of both was 48 g. 2. A Toyo Seiki Plastomill was set in an air atmosphere at a temperature of 200°C and a rotation speed of 30 rpm. 3. The resin raw material composition prepared in step 1 was quickly added, and kneading was started immediately. The time when the raw material addition was completed was set to 0 minutes. 4. The time from when the kneading torque of the Plastomill started to when it reached its peak was measured. This measurement method is an index of the ease of kneading (dispersibility) in an actual extruder. In general extrusion molding, the resin raw material must start to melt in the extruder in a short time and the screw torque must rise. If the torque rise is slow, the extruder's kneading ability is not fully utilized, resulting in poor dispersion. The dispersibility was evaluated based on the torque rise time according to the following criteria. A 150 seconds or less B: Over 150 seconds and up to 200 seconds C More than 200 seconds but not exceeding 300 seconds D. More than 300 seconds
[0084] <Bulk density variation> The measurement was performed by the following method according to JIS-Z2504. 20 kg of the resin raw material composition according to the present disclosure was charged into a raw material hopper having a height of 600 mm, a diameter of 400 mm at the top, and a diameter of 250 mm at the bottom, a hemispherical dome at the bottom, and an opening for extracting raw material from the bottom end of the dome. Immediately after charging, the resin was extracted five times from the top surface of the raw material with a 200 cc cup, and the first bulk density was calculated from the average weight. Next, 15 kg of raw material was extracted from the opening at the bottom of the hopper, and the second bulk density was then calculated in the same manner. At this time, the bulk density ratio (first bulk density / second bulk density) was used as the variation in bulk density. Evaluation was performed as follows. A The bulk density ratio is in the range of 0.95 or more and 1.05 or less. B The bulk density ratio is within the range of more than 0.90 and less than 0.95, or more than 1.05 and not more than 1.10. C The bulk density ratio is less than 0.90 or more than 1.10.
[0085] <Classification> 200 g of the resin raw material composition according to the present disclosure was sampled and randomly placed in a cylindrical polyethylene sample bottle with an outer diameter of 79 mm and a capacity of 500 cc. This was shaken for 5 minutes with a commercially available small shaker (Kenis Co., Ltd., Kenis Mini Shaker 3D 33180556, shaking width of about 7 degrees, shaking speed of 30 rpm). Then, 10 g of the resin raw material composition was sampled from the top of the bottle (within a range of about 1 / 10 of the height) and the bottom of the bottle (within a range of about 1 / 10 of the height), and the number of pellet particles therein was counted and the number ratio (top / bottom) was measured. In this case, the number ratio of the pellets with good classification properties was close to 1.0. The evaluation was as follows. A The number ratio is 0.9 or more and less than 1.1. B The number ratio is within the range of 0.85 or more and less than 0.9, or greater than 1.1 and less than 1.15. C The number ratio is less than 0.85 or more than 1.15.
[0086] <Angle of repose> It was determined using a device conforming to JIS9301-2-2. 200g of sample was fed from a height of about 40mm from the top edge of the funnel at a speed of 20g to 60g per minute. The falling speed was kept constant. 200g of sample was fed from the funnel, and the angle between the inclined surface of the sample and the horizontal plane was measured with a protractor. It was evaluated as follows. A The angle is within the range of 30° to 55°. B. The angle is less than 30° or more than 55°.
[0087] <Dust generation (dust generation)> 500cc of the resin raw material composition was placed in a measuring cup and dropped from a height of 30cm onto a rectangular piece of black paper with one side measuring 30cm or more. Five seconds after the drop, the amount of dust that flew up was visually observed from the side and judged. A black board was placed in the background to make it easier to see the dust that flew up. Evaluation was based on the following criteria. A: There is no lifting at all, or if any lifts, it is no more than 15cm high. B The rise occurs at a height of more than 15 cm.
[0088] <Piping transportability> 5 kg of the resin raw material composition to be measured was prepared and transported to a height of 2 m using a pneumatic transport autoloader connected to a 10 m long polyvinyl chloride hose. The ratio of the bulk density before and after transport (before transport / after transport) was measured in the same manner as in the measurement method for <bulk density> described above. A The bulk density ratio is in the range of 0.95 or more and 1.05 or less. B The bulk density ratio is within the range of more than 0.90 and less than 0.95, or more than 1.05 and not more than 1.10. C Bulk density ratio is less than 0.90 or more than 1.10
[0089] <Fisheyes in molding resin raw material composition> The molding resin raw material composition was put into a twin-screw extruder with a shaft diameter of 30 mm and L / D of 35, kneaded at a predetermined temperature (230°C), extruded through a 300 mm T-die, and cooled with a cast roll to obtain an unstretched raw roll with a thickness of 1 mm. This raw roll was cut into 8 mm x 8 mm pieces and stretched 4 times x 4 times with a batch-type biaxial stretching machine to form a film. The stretched film was cut into 20 cm x 20 cm pieces, and fish eyes with a diameter of 0.5 mm or more were counted. The evaluation was converted to a value per 10 g of film. A: 5 fish eyes or less per 10g B: Fish eyes: 6-20 / 10g C The number of fish eyes exceeds 20 per 10g.
[0090] <Fisheyes in the resin raw material composition for microporous membrane> A resin raw material composition for a microporous membrane containing liquid paraffin as a plasticizer was mixed with additional liquid paraffin as a plasticizer, and the amount of liquid paraffin was adjusted to 65% by weight after mixing. The raw material was fed into a twin-screw extruder with a shaft diameter of 30 mm and L / D of 35, kneaded at a predetermined temperature (230°C), extruded through a 300 mm T-die, and cooled with a cast roll to obtain an unstretched raw material with a thickness of 0.5 mm. This raw material was cut into 8 mm x 8 mm and stretched 7 times x 7 times with a batch-type biaxial stretching machine to form a film. The stretched film was further immersed in an excess amount of dichloromethane and then dried to extract and remove the plasticizer, thereby obtaining a microporous membrane. The obtained microporous membrane was cut into 20 cm x 20 cm, and fish eyes with a diameter of 0.5 mm or more were counted. The evaluation was converted to a value per 10 g of microporous membrane. A: 5 fish eyes or less per 10g B: Fish eyes: 6-20 / 10g C The number of fish eyes exceeds 20 per 10g.
[0091] <Microporous membrane thickness (μm)> The thickness of the sample was measured at an ambient temperature of 23±2° C. using a Toyo Seiki Micro Thickness Meter (type KBN, terminal diameter Φ5 mm, measurement pressure 62.47 kPa).
[0092] <Porosity of microporous membrane (%)> The basis weight W (g / cm) was calculated from the mass of a 100 mm square microporous membrane sample. 2 ) and the average density ρ (g / cm) of the components (resin and additives) that make up the microporous membrane 3 ) was calculated from the thickness d (cm) of the microporous membrane using the following formula: Porosity = (W / (d × ρ)) × 100 (%) The ratio of porosity of each layer (porosity of layer A / porosity of layer B) For example, in the case of a three-layer film of A layer / B layer / A layer, if peeling is possible, peel it off and measure it by the above method. In the case of the wet method, peeling may not be possible, in which case, the volume concentration P of the solvent charged in each layer (P for A layer) is used. A , B layer is P B ), and the thickness D (thickness of layer A is D A , B layer thickness is D B ) was measured, and the porosity of layer A was measured as V A , the porosity of layer B is V B The equation was calculated by simultaneously solving the following two equations. Equation 1: Total layer porosity = (P A ×D A ×Number of layers 2+P B ×D B × Number of layers 1) / Total layer thickness Equation 2...(V A / V B )=(P A / P B )
[0093] <Air permeability of microporous membrane (sec / 100cc)> Measurements were made in accordance with JIS P-8117 using a Gurley air permeability meter "G-B2" (trademark, manufactured by Toyo Seiki Seisakusho, Ltd.) The values in the table are 20 μm equivalent air permeabilities calculated by proportional calculation based on the total thickness.
[0094] <Puncture strength of microporous membrane (g)> The compression strength was determined by carrying out a puncture test using a handy compression tester "KES-G5" (trademark, manufactured by Kato Tech) under conditions of a needle tip curvature radius of 0.5 mm and a puncture speed of 2 mm / sec.
[0095] Examples 1.1 to 1.18 The pellets, powders and liquids in Tables 1, 2 and 3 were used in the combinations in Table 4 to prepare molding resin raw material compositions according to the following process. (a) A specified amount of pellets was placed in an 80-liter tumbler mixer, and then the liquid component was placed on top of the pellets. The liquid component was placed in the center of the mixer, so as not to adhere to the mixer walls. The mixture was then stirred for 10 minutes. (b) Then, a specified amount of powder was added and stirred for another 10 minutes. PL / PW / LQ were added in the composition ratios shown in Tables 4 and 5 so that the total amount was 20 kg. In Examples 1.1 to 1.18, there was no stickiness, and the number of granular bodies including aggregates of 10 or more resin pellets was 20% or less. The dispersibility, piping transportability, classifiability, and dust generation of this molding resin raw material composition were all good. The variation in bulk density (classifiability), angle of repose, and fisheye were all good.
[0096] The solid line in Fig. 3 shows the torque rise time in Example 1.1. The average torque reaches its peak about 100 seconds after the raw material is charged (kneading starts), and it is clear that the dispersibility is better than that of Comparative Example 1.1 (about 180 seconds).
[0097] Comparative Examples 1.1 to 1.5 In Comparative Example 1.1, a molding resin raw material composition was prepared by dry blending the powder and pellets with the same composition as in Example 1.4 without adding LQ. Since there was no LQ, the powder and pellets were completely separated, and they were classified during transportation and in the hopper, and dust was also flying. The manufacturing method of Comparative Example 1.2 was based on the same method as in Example 1.1, but since the composition was outside the scope of this disclosure, the performance was insufficient. The dashed line in Figure 3 indicates the torque rise time in Comparative Example 1.2. The average torque reached its peak about 180 seconds after the raw material was added (kneading started), and it can be seen that the dispersibility was poorer than in Example 1.1 (about 100 seconds). Comparative Examples 1.3 and 1.4 were similar to Example 1.1 except for the composition. Comparative Example 1.5 had the same composition as Example 1.4, but in step a, all the raw materials were added at once and stirred for 20 minutes, and step b was not performed. In Comparative Example 1.3, the adhesion between the powder and pellets was insufficient, and classification and dust were generated. In Comparative Example 1.4, the liquid component was excessive and sticky. As a result, a large amount of PWL10 particles and PWL0 particles were generated. In Comparative Example 1.5, all the raw materials of pellets, powder, and liquid components were stirred at once, so no single particles were generated and all were PWL10 or higher. As a result, the dispersibility and piping transportability were significantly poor.
[0098] [Table 1] LDPE: Low-density polyethylene (viscosity average molecular weight 70,000) HDPE1: High density polyethylene (viscosity average molecular weight 200,000) PP: Polypropylene (viscosity average molecular weight 950,000) EL: Elastomer (viscosity average molecular weight 60,000)
[0099] [Table 2]
[0100] [Table 3]
[0101] [Table 4]
[0102] [Table 5]
[0103] Examples 2.1 to 2.22 The pellets, powders (resin powders, fillers) and liquids in Tables 6, 7 and 8 were used in the combinations shown in Tables 9 and 10 to prepare resin raw material compositions for microporous membranes according to the following process. Step (a'): A predetermined amount of pellets was placed in a tumbler mixer, and the liquid component was placed on top of the pellets. The liquid component was placed in the center of the mixer so as not to adhere to the mixer walls. The mixture was then stirred at 15 rpm for 10 minutes. Step (b'): A predetermined amount of powder was then added and stirred for another 10 minutes. PL / PW / LQ were added in the composition ratios shown in Tables 9 and 10 so that the total amount was 20 kg. When the lid of the mixer was opened once, many pellets were found to be attached to the wall of the mixer, but these were dropped into the mixer with a spatula or the like and stirred for another 5 minutes, and a generally uniform resin raw material composition for microporous membrane was obtained. The dispersibility, piping transportability, classifiability, and dust generation of this resin raw material composition for microporous membrane were all good. The variation in bulk density (classifiability), angle of repose, and fisheye were all good. The results are shown in Tables 9 and 10.
[0104] In Examples 2.1, 2.2, and 2.4 to 2.10, the resin raw material compositions for microporous membranes shown in Tables 9 and 10 were used as they were. In Examples 2.3 and 2.11 to 2.22, after obtaining the resin raw material compositions for microporous membranes shown in Tables 9 and 10, the powders shown in Tables 11 and 12 were additionally added and blended in step (c') to obtain mixed compositions. Good blending was also achieved in step (c').
[0105] The resin raw material composition for a microporous membrane or the mixed composition prepared above was fed into a twin-screw extruder with a screw diameter of 44 mm. In Examples 2.3 and 2.11 to 2.22, since the pellets were already coated with powder, even when additional powder was added in step (c') and fed into the twin-screw extruder, no classification occurred and a good mixed state was maintained.
[0106] Liquid paraffin was added as a plasticizer from the middle of the cylinder of the extruder. The polymer content during extrusion after adding liquid paraffin was calculated by the following formula: {total mass (g) of resin components / total mass (g) of composition after adding liquid paraffin} × 100 (mass%), and was adjusted to be 33 mass%. The extrusion temperature was 200°C, and the sheet-like molten resin extruded from the T-die at the tip of the extruder was introduced into a cast roll with a roll temperature of 90°C, cooled and solidified, and an unstretched raw material of a predetermined thickness was obtained. Furthermore, this unstretched raw material was introduced into a biaxial stretching machine and simultaneously biaxially stretched 7 times vertically and 7 times horizontally at a temperature of 120°C, and then the plasticizer was extracted and removed with methylene chloride. This was further introduced into a heat treatment device to obtain a microporous film. The heat treatment temperature was adjusted in the range of 130 to 135°C. The thickness was adjusted to about 9 μm. This microporous membrane had good resin dispersion and was also good in terms of air permeability, pin puncture strength, etc. as a microporous membrane. The results are shown in Tables 11 and 12. The membrane formation results of Examples 2.1 to 2.22 show that the resin raw material composition for a microporous membrane of the present disclosure has no problems in membrane formability and product properties of the microporous membrane.
[0107] Comparative Examples 2.1 to 2.5 In Comparative Example 2.1, a resin raw material composition for a microporous membrane was prepared by dry blending the powder and pellets with the same composition as in Example 2.4 without adding LQ. Since there was no LQ, the powder and pellets were completely separated, and they were classified during transportation and in the hopper, and dust was also flying. The manufacturing methods of Comparative Examples 2.2 to 2.4 were based on the same method as in Example 2.1, but the performance was insufficient.
[0108] Comparative Examples 2.3 and 2.4 are the same as Example 2.1 except for the composition. In Comparative Example 2.5, all the raw materials were added at once in step a and stirred for 20 minutes, and step b was not performed. In Comparative Example 2.3, the powder did not bond to the pellets sufficiently, resulting in classification and dust. In Comparative Examples 2.4 and 2.5, both had an excess of liquid components and were sticky. As a result, a large amount of PWL10 particles and PWL0 particles were generated. In Comparative Example 2.5, all the raw materials, including pellets, powder, and liquid components, were stirred at once, so that no single particles were generated and all were PWL10 or higher. As a result, the dispersibility and piping transportability were significantly poor.
[0109] For Comparative Examples 2.1 to 2.5, the resin raw material compositions for microporous membranes shown in Tables 9 and 10 were used as is to confirm the film-forming properties and physical properties of the microporous membranes. These had problems with the dispersion of the raw material compositions, and the film was produced by devising the way in which they were fed into the extruder. Poor dispersion was confirmed in all cases, and Comparative Example 2.4 in particular had severe poor dispersion, with numerous fish eyes and a significantly lower puncture strength than the others.
[0110] 《Reference example》 Only the powder (PW2) shown in Table 7 was used to prepare a resin raw material composition for a microporous membrane, and the dispersibility, transportability through pipelines, classifiability, dust generation, variation in bulk density, angle of repose, and fisheyes were evaluated.
[0111] [Table 6] HDPE1: High density polyethylene (viscosity average molecular weight 200,000) PP: Polypropylene (viscosity average molecular weight 950,000) EL: Elastomer (viscosity average molecular weight 60,000)
[0112] [Table 7]
[0113] [Table 8]
[0114] [Table 9]
[0115] [Table 10]
[0116] [Table 11]
[0117] [Table 12] [Industrial Applicability]
[0118] The resin raw material composition of the present disclosure has good dispersibility, piping transportability, and moldability, and can produce molded products with little dust generation and classification, and with good physical properties. For example, in the production of packaging films and microporous films, in applications in which powder and pellets are simultaneously subjected to extrusion molding, the components of the pellets and powder have good dispersibility, no dust is generated even after blending the powder and pellets, and the powder can be transported well without classification or adhesion to the pipe during piping transportation, no classification occurs in the hopper, and extrusion molding is also good, and molded products with very few fish eyes in the obtained films and microporous films can be obtained. This has industrial applicability, for example, as packaging films with excellent moldability and dispersibility, and separators for lithium ion secondary batteries, etc. [Explanation of symbols]
[0119] 10 Resin raw material composition of the present disclosure 20 Conventional resin raw material composition
Claims
1. A resin raw material composition comprising resin pellets (PL), powder (PW) and a liquid component (LQ), The resin raw material composition is a molding resin raw material composition, The resin pellets contain a polyolefin, The powder is inorganic particles, The average particle size of the powder is 1 μm or more and 10 μm or less, The liquid component is liquid paraffin, At least a part of the surface of the resin pellet is coated with the liquid component, the resin pellet coated with the liquid component is a single particle or an aggregate of multiple particles, and the powder is attached to the liquid component, the resin pellet including a granular body, a ratio of the mass% of the resin pellets to the mass% of the powder (PL / PW) is 18 or more and 99 or less, and a ratio of the mass% of the resin pellets to the mass% of the liquid component (PL / LQ) is 18 or more and 199 or less, based on the total mass of the resin raw material composition; A resin raw material composition, wherein the number of the granular bodies containing a single resin pellet is 99% or more based on the total number of the granular bodies.
2. A resin raw material composition comprising resin pellets (PL), powder (PW) and a liquid component (LQ), The resin raw material composition is a resin raw material composition for a microporous membrane, The resin pellets contain a polyolefin, The powder is inorganic particles, The average particle size of the powder is 1 μm or more and 10 μm or less, The liquid component is liquid paraffin, At least a part of the surface of the resin pellet is coated with the liquid component, the resin pellet coated with the liquid component is a single particle or an aggregate of multiple particles, and the powder is attached to the liquid component, the resin pellet including a granular body, a ratio of the mass% of the resin pellets to the mass% of the powder (PL / PW) is 18 or more and 99 or less, and a ratio of the mass% of the resin pellets to the mass% of the liquid component (PL / LQ) is 18 or more and 199 or less, based on the total mass of the resin raw material composition; A resin raw material composition, wherein the number of the granular bodies containing a single resin pellet is 99% or more based on the total number of the granular bodies.
3. 3. The resin raw material composition according to claim 1, comprising, as a main component, granules in which the powder is adhered to the liquid component of the resin pellets coated with the liquid component.
4. A resin raw material composition described in any one of claims 1 to 3, wherein granular bodies having a particle size of 10 mm or more account for 1 mass % or less based on the total mass of the resin raw material composition.
5. A resin raw material composition described in any one of claims 1 to 4, wherein the maximum diameter of a granular body containing a single particle of the resin pellet is greater than or equal to the particle size of the resin pellet and is less than or equal to the particle size of the resin pellet + 5 mm.
6. The number of granular bodies including agglomerates of a plurality of the resin pellets is less than 30% based on the total number of the granular bodies, and The resin raw material composition according to any one of claims 1 to 5, wherein, when the resin raw material composition further contains granules consisting of the powder and the liquid component not containing the resin pellets, the number of granules not containing the resin pellets is less than 20% based on the total number of granules.
7. The resin raw material composition according to any one of claims 1 to 6, wherein the number of granules containing aggregates of 10 or more of the resin pellets is 1% or less based on the total number of granules.
8. The resin raw material composition according to any one of claims 1 to 7, wherein the variation in bulk density of the resin raw material composition is 10% or less.
9. The resin raw material composition according to any one of claims 1 to 8, wherein the resin raw material composition has an angle of repose of 30° or more and 55° or less.
10. A method for producing a resin raw material composition, comprising: The resin raw material composition is a molding resin raw material composition according to claim 1, a coating step of kneading the resin pellets and the liquid component in a blender to coat at least a part of the surface of the resin pellets with the liquid component; an adhesion step of adding the powder to the blender after the coating step, further kneading the powder, and adhering the powder to the liquid component of the resin pellets coated with the liquid component; A method for producing a resin raw material composition comprising the steps of:
11. The method for producing a resin raw material composition according to claim 10, wherein a torque rise time is 150 seconds or less.
12. A method for producing a resin raw material composition, comprising: The resin raw material composition is a resin raw material composition for a microporous membrane according to claim 2, a coating step of kneading the resin pellets and the liquid component in a blender to coat at least a part of the surface of the resin pellets with the liquid component; an adhesion step of adding the powder to the blender after the coating step, further kneading the powder, and adhering the powder to the liquid component of the resin pellets coated with the liquid component; A method for producing a resin raw material composition comprising the steps of:
13. The method for producing a resin raw material composition according to claim 12, wherein a torque rise time is within 150 seconds.
14. A step of producing a resin raw material composition by the method for producing a resin raw material composition according to claim 12 or 13; A step of further mixing the resin raw material composition with resin pellets (PL) and / or powder (PW), which are the same as or different from the resin pellets (PL) and the powder (PW); A method for producing a mixed composition comprising the steps of:
Citation Information
Patent Citations
JP1975095363A
Extruder for molten resin
JP1984039536A
Production of thermoplastic resin containing liquid additive
JP1986188424A
Kneading method
JP1988147609A
Polyolefin fine porous film and method of manufacturing the same
JP2002194132A